Management of commercial bank funds - McKinney, George Wesley; Brown, William James (New York : American Institute of Banking, 1974)
Management of bank's fund is one of the most important responsibilities of bank management.
Includes index.
Includes bibliographical references: p. 287-291.
II 15/01/2019
Loans
Keywords: Bank management